The Great Maya Droughts in Cultural Context : Case Studies in Resilience and Vulnerability - Iannone, Gyles (Book collections on Project MUSE., 2014)
"In The Great Maya Droughts in Cultural Context, contributors reject the popularized link between societal collapse and drought in Maya civilization, arguing that a series of periodic "collapses," including the infamous Terminal Classic collapse (AD 750-1050), were not caused solely by climate change-related droughts but by a combination of other social, political, and environmental factors. New and senior scholars of archaeology and environmental science explore the timing and intensity of droughts and provide a nuanced understanding of socio-ecological dynamics, with specific reference to what makes communities resilient or vulnerable when faced with environmental change. Contributors recognize the existence of four droughts that correlate with periods of demographic and political decline and identify a variety of concurrent political and social issues. They argue that these primary underlying factors were exacerbated by drought conditions and ultimately led to societal transitions that were by no means uniform across various sites and subregions. They also deconstruct the concept of "collapse" itself--although the line of Maya kings ended with the Terminal Classic collapse, the Maya people and their civilization survived. The Great Maya Droughts in Cultural Context offers new insights into the complicated series of events that impacted the decline of Maya civilization. This significant contribution to our increasingly comprehensive understanding of ancient Maya culture will be of interest to students and scholars of archaeology, anthropology, geography, and environmental studies"--